Structural and Optical Properties of Mn Doped ZnO Nanoparticles - A. Alkhtaby, Lila; Husain, Shahid; Khan, Wasi; Alim H. Naqvi, S. (Asian Journal of Chemistry, 2011)
Manganese doped zinc oxide nanoparticles have been synthesized by the sol-gel method under acid-base reaction followed with pH value 9 to form Zn1-xMnxO for different values of x = 0.01, 0.02 and 0.03. The samples are characterized with powder X-ray diffraction and ultraviolet/ visible (UV/V) spectroscopy. All samples are found in single phase with polycrystalline nature having wurtzite lattice structure. The UV/V spectra of the nanoparticles indicate a decrease in the band gap from 3.08 eV (for 1 % Mn doped) to 3.05 eV (2 % Mn doped), whereas it increases to 3.11 eV for 3 % doping. The results reveal the lattice strain associated with Mn concentration.